PENGARUH SELF EFFICACY TERHADAP KINERJA KARYAWAN - Cita LW, Dila Agestian (POLITEKNIK NEGERI BANDUNG, 2016)
Human resources have a major role in every activity of the company. The company's goal will be achieved by creating a good employee’s performance. One of the factors that affect the employee's performance is self-efficacy (a person's beliefs about the ability and chances to successfully achieve a certain task). Employees of the company should have high self-efficacy so it can improve the company performance because self-efficacy will encourage someone more eager to achieve optimal results in their performance. The good or poor employee performance can be determined by performance appraisal of employees based on the standard that has been set. The purpose of this research is to know employees self-efficacy, the employee's performance at PT Sandy Globlino (SND), and to determine the effect of self-efficacy to employees performance at PT Sandy Globlindo (SND). This research use probability sampling technique, with 101 samples and spreading questionnaire using a Likert scale with interval data (1-5) to get data. Methods of data analysis used in this research include the classic assumption test, descriptive analysis, correlation analysis, hypothesis testing, regression analysis, and coefficient determination. The results of this research is self-efficacy of employees at PT Sandy Globlindo (SND) has self-efficacy with levels of good or high, the performance of employees at PT Sandy Globlindo (SND) have levels of good or high, and the results show that there is a positive and strong relationship between self-efficacy to employees performance in PT Sandy Globlindo (SND) with a correlation value of 0.746. Other than that obtained results that Y = 31.328 + 0,746X which means that if self-efficacy increased one unit then the performance of employees will increase by 0.746 units. This research also obtained results that self-efficacy able to explain the performance of SND’s employees by 55.7% and 44.3% explained by other factors not examined in this study.